2014
DOI: 10.1080/02786826.2014.984801
|View full text |Cite
|
Sign up to set email alerts
|

New Particle Formation and Growth in an Isoprene-Dominated Ozark Forest: From Sub-5 nm to CCN-Active Sizes

Abstract: This study presents results of new particle formation (NPF) and the growth of new particles to cloud condensation nuclei (CCN)-active sizes (»100 nm) observed during this field campaign. The measured sub-5 nm particles were up to »20,000 cm ¡3 during a typical NPF event. Nucleation rates J 1 were relatively high (11.0 § 10.6 cm ¡3 s ¡1 ), and one order of magnitude higher than formation rates of 5 nm particles (J 5 ). Sub-5 nm particle formation events were observed during 64% of measurement days, with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 80 publications
(84 reference statements)
4
35
0
Order By: Relevance
“…J 1.5 ranged from 10 −2 to 0.8 cm −3 s −1 and strongly correlated with the measured sulfuric acid concentration. These results are consistent with previous observations in the U.S. that sub‐2 nm particles exist only in the presence of sulfuric acid [ Yu et al ., 2013; Yu et al ., ]. However, our results contrast with the reports from the Hyytiälä boreal forest, where a constant pool of sub‐2 nm particles was observed during the day and night independent of sulfuric acid concentration [ Kulmala et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…J 1.5 ranged from 10 −2 to 0.8 cm −3 s −1 and strongly correlated with the measured sulfuric acid concentration. These results are consistent with previous observations in the U.S. that sub‐2 nm particles exist only in the presence of sulfuric acid [ Yu et al ., 2013; Yu et al ., ]. However, our results contrast with the reports from the Hyytiälä boreal forest, where a constant pool of sub‐2 nm particles was observed during the day and night independent of sulfuric acid concentration [ Kulmala et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…High isoprene emission fluxes and mixing ratios during most of the measurement campaign played a potentially major role in atmospheric chemistry at this site. Monoterpenes, which had lower emission fluxes but have higher aerosol yields, contributed to atmospheric particle growth along with isoprene (Yu et al, 2014). Maximum isoprene fluxes measured at this Missouri forest during this study in 2012 (35.4 mg m À2 h À1 ) and in 2011 by Potosnak et al (2014;53.3 mg m À2 h À1 ) are the highest ever reported for a forest canopy, surpassing fluxes of up to 30 mg m À2 h À1 previously reported from an oil palm plantation in Borneo (Misztal et al, 2011).…”
Section: Voc Measurements In Contextmentioning
confidence: 99%
“…Both laboratory (Kirkby et al, ; Riccobono et al, ; Tröstl et al, ; Zhao et al, ) and field (Bianchi et al, ) studies have revealed the role of oxidized organic vapors in the nucleation and initial particle growth. Other studies have reported the contributions of the condensation of low volatility biogenic organic vapors to the growth of newly formed particles in the CCN size range (e.g., Yu et al, ; Zhou et al, ). In Amazon, where new particle formation (NPF) events were only observed in the wet season in an open pasture site (Wimmer et al, ), the enhancement of the solute mass is expected to be the main mechanism through which BSOA contribute to CCN number concentrations.…”
Section: Introductionmentioning
confidence: 99%